Modelling the Rainfall Erosivity of the Rhone Region (Southeastern France) Associated with Climate Variability and Storminess - Nazzareno Diodato; Gianni Bellocchi; Nunzio Romano; Francesco M. Guadagno (Advances in Meteorology)
Changes in the spatial and temporal patterns of extreme rainfall may have important effects on the magnitude and timing of rainfall erosivity, which in turn lead to even severe soil degradation phenomena. The Mediterranean belt is characterized by strong climatic variability and specific seasonal features, where dry periods are often interrupted by pulsing storms. Identifying the thresholds associated with extreme rainfall events is among the most important challenges for this region. To discern the spatial patterns of rainfall erosivity hazard in the Rhone region (eastern France), this study establishes thresholds in the power of rainstorms. An indicator Kriging approach was employed for computing probability maps of the annual rainfall erosivity exceeding the threshold of 1800 MJ mm ha−1 h−1, the latter being twice greater than the standard deviation. The interdecadal spatial patterns of hazard were assessed for recent decades (1991–2010) and the precedents ones (1961–1990). Climate fluctuations of rainfall erosivity revealed possible signals of increased storminess hazard across the region in recent times. We also discussed changes in the rainfall erosivity hazard forcing as related to climatic changes in daily rain rate, especially in autumn when the erosivity is likely affected by more intense storminess occurring across the southern part of the Rhone region.